Acridine Orange Fluorescence Stain for the Diagnosis of Malarial Parasite - Siddique, Md A; Alam, Md A; Sultan, Md Tipu; Uddin, Md Q; Hossain, SMA; Naaz, S (TAJ: Journal of Teachers Association, 2009)
A total of six hundred suspected cases of malaria (150 from each centre of Rajshahi Medical College Hospital and three thanas under Rajshalhi district viz. Paba, Godagari and Charghat) were examined through both thick and thin film preparation and stained by both Giemsa and acridine orange fluorescence staining respectively. All the slides in both stained preparation were examined by three competent microbiologists in three different centres. Malarial parasite detection in cases of Rajshahi Medical College Hospital. Paba, Godagari and Charghat. In Giemsa staining parasites were positive in 14 (9.33%), 16(10.66%),26(17.33%) and 41(27.33%) cases respectively while it was found to be positive in 21(14.00%), 36(24.00%),49(32.66%) and 61(40.66%) cases in acridine orange fluorescence staining respectively. In comparison acridine orange fluorescence staining was found to be more sensitive over Giemsa staining especially in low parasitaemic cases. doi: 10.3329/taj.v16i2.3883 TAJ December 2003; Vol.16(2): 58-61